Elementary School Teachers' Readiness to Engage in Distance Learning and Training during the COVID-19 Pandemic - Yudi Yanuar; Wawan Setiawan; Wahyu Sopandi; Atep Sujana; Mohamad Adning (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractThe readiness of elementary school teachers during the COVID-19 pandemic to engage in distance learning is the basis for developing a training mode for teachers. This study aims to ensure the readiness of elementary school teachers to participate in distance learning and training during the COVID-19 pandemic. In this study, descriptive quantitative is used with online survey techniques. The research subjects were 85 elementary school teachers in Indonesia who voluntarily filled out a questionnaire. The data were collected through a questionnaire instrument with a Likert scale and open-ended questions. The data were analyzed by calculating the average of each item and making a percentage. Research findings indicate that 37.22% of the respondents were ready to engage in distance learning and training with a blended mode. They used various applications such as WhatsApp, Google Classroom, Google Form, and YouTube.Keywords: teachersâ€™ readiness, elementary school, distance learning, training.Â AbstrakKesiapan guru SD di masa pandemi COVID-19 untuk mengikuti pembelajaran jarak jauh menjadi dasar pengembangan model pelatihan bagi guru. Penelitian ini bertujuan untuk memastikan kesiapan guru sekolah dasar untuk mengikuti pembelajaran dan pelatihan jarak jauh selama pandemi COVID-19. Dalam penelitian ini digunakan deskriptif kuantitatif dengan teknik survei online. Subyek penelitian adalah 85 guru sekolah dasar di Indonesia yang secara sukarela mengisi angket. Pengumpulan data dilakukan melalui instrumen angket dengan skala likert dan pertanyaan terbuka. Data dianalisis dengan menghitung rata-rata setiap item dan membuat persentase. Temuan penelitian menunjukkan bahwa 37,22% responden siap untuk terlibat dalam pembelajaran dan pelatihan jarak jauh dengan mode campuran. Mereka menggunakan berbagai aplikasi seperti WhatsApp, Google Classroom, Google Form, dan YouTube.Kata kunci: kesiapan guru, sekolah dasar, pembelajaran jarak jauh, pelatihan.